Legal Qualification of the Armed Conflict in Syria - KHANFRI, Meriam (Journal of Human Sciences, 2025)
The legal qualification of armed conflicts is a complex and challenging issue due to its connection with several factors, such as the principle of sovereignty, the use of lethal weapons, the involvement of external parties, and the emergence of new types of conflicts where it is difficult to distinguish combatants from non-combatants. Considering the link between the protection afforded to victims and the legal classification of the conflict, which aims at the optimal implementation of the rules of international humanitarian law, and given the complex and evolving nature of the Syrian conflict, this paper examines the legal qualification of the armed conflict in Syria: Is it a non-international armed conflict, thus requiring the application of the standards stipulated in Common Article 3 of the 1949 Geneva Conventions and Additional Protocol II of 1977? Or is it an internationalized armed conflict, exhibiting elements characteristic of both international and non-international armed conflicts? This study adopts a descriptive analytical methodology that examines international conventions and resolutions, analyzes their content, and elucidates the position of legal scholars and international practice regarding the qualification of the conflict in Syria.